Two years follow up study of post placental insertion of IUCD during caesarean sections: safety, efficacy and complications - Pandher, Dilpreet Kaur; Rani, Shikha; Goel, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The present study evaluates safety, efficacy, expulsion rate and complications of PPIUCD insertion in women undergoing caesarean section in a medical college for 2 years period. Methods: This is a prospective cohort study done over a 2 year period. Total 185 patients undergoing caesarean section and fulfilling medical eligibility criteria for PPIUCD were enrolled in the study. The followup of these patients was done at 6 weeks, 6 months and 1-2 years. Results: Thirteen patients (7%) lost to follow up so final outcome analysis was done in 172 patients. The problems encountered were spontaneous expulsion in 4 patients, removal due to heavy menstrual flow in 13 patients, non-visibility of threads in 4 patients, discharge per-vaginum in 1 patient and pain lower abdomen in 1 patient. Voluntary removal was done in 3 patients by 2 years who wished to conceive. The successful continuation rate came out to be 84.9% by 2 years. There was no failure reported in terms of intra-uterine or extra-uterine pregnancy and no increased risk of infection or perforation over the 2 years follow up. Conclusions: Immediate post-placental IUCD insertion is safe and effective method of contraception with no need to wait for 6 weeks which thereby reduces unwanted pregnancy rates. Mild discomfort and the minor post procedure complaints are taken care of well in puerperium. Higher rate of expulsion can be taken care of by early follow-up with regular visits and offering other safe and effective method of contraception.